Assessing environmental damage to marine protected area: a case of Perhentian Marine Park in Malaysia - Md. Nurul Islam, Gazi; Mohd Noh, Kusairi; Tai, Shzee Yew; Mohd Noh, Aswani Farhana (Canadian Center of Science and Education, 2013)
The Perhentian Island located in the East coast of Peninsular Malaysia is well-known for its rich coral reef ecosystems. Marine resources of Malaysia have been overexploited due to overfishing and tourism activities. As such no-take marine protected area (MPAs) were established in Malaysia, including Perhentian Island Marine Park to enable overexploited marine resources to recover and to conserve coral reef ecosystems. This paper examines the current level of activities causing damage to coral reef habitats in the Perhentian MPA. This study used paired comparison method to elicit the perception of local stakeholders on activities harmful to the marine habitats. The results of the analysis showed that various respondent groups had similar preference rankings on the harmful activities: littering, discarding fishing equipment, excess fishing and too many divers that cause damage to habitats in the MPA area. The findings suggest that policy makers should take cognizance of the local stakeholders’ concern in planning and designing of marine protected areas in Malaysia.